Psychological Distress Among Health Care Workers in Health Facilities of Mettu Town During COVID-19 Outbreak, South West Ethiopia, 2020 - Hajure, Mohammedamin; Dibaba, Bekem; Shemsu, Shuayib; Desalegn, Defaru; Reshad, Mohammed; Mohammedhussein, Mustefa (Frontiers in Psychiatry, 2021)
Background: During any of the outbreak, health care workers were at increased risk, and many were quarantined, which resulted in psychological distress. Therefore the study aimed to assess the psychological distress related to COVID-19 among health care workers in Mettu town during the outbreak of an epidemic. Methods: A facility-based cross sectional study was conducted from May 1- 15, 2020 using convenient sampling techniques among 127 health care providers during COVID 19 in Mettu town, south west Ethiopia. Self-administered questionnaire was used to collect information. Depression and anxiety were assessed as subscales from the short version of the Depression Anxiety Stress Scale (DASS-21). The psychological distress of COVID-19 was measured using the Impact of Event Scale Revised (IES-R). Data analysis was done using SPSS version 24. Chi-square was used to find the association between binary score of psychological distress and independent variables. Multivariable logistical regression analysis was used to evaluate the significance of the relationship. Variables with a P value < 0.05 in the final fitting model were declared to be associated with the outcome variable. Result: Overall, 40.2% of all participants reported symptoms of psychological distress using IES-R scale. Also, considering the level of psychological distress, the majority of the participants reported mild psychological distress (37%) followed by moderate psychological distress (29%). The multivariate logistic regression analysis revealed that the odds of psychological distress were higher among health care providers who had depression and those who used alcohol, khat and tobacco in the past three months shows significant association with psychological distress. Conclusion: Our findings revealed that the COVID 19 outbreak had caused a major psychological distress on health care providers. So the findings, seek attention for early psychological intervention needed to manage psychological distress in health care providers regarding identified factors.